Reflux Aspiration and Lung Disease (Springer International Publishing, 2018)
This book is about the interface between reflux and the respiratory tract. Reflux is an important factor in many different lung diseases. The pathological basis of reflux has recently undergone major changes in our understanding based on improved diagnostic technology. Readers will learn about how reflux impacts on many common lung conditions. Special circumstances such as eosinophilic inflammation in relation to asthma, cough, and eosinophilic bronchitis will be highlighted. Particular attention is also given to previously unrecognised role of non-acid "airway" reflux. Additionally, pharmacological, surgical and behavioural techniques for diagnostic and treatment are explored witin these chapters This book offers a comprehensive overview of various research areas in reflux in relation to airways disease, since currently there is no summary of how the different but overlapping areas impacted by reflux affect the respiratory tract. It will be of great interest to respiratory physicians, otorhinolaryngologists, and gastroenterologists. .